Molecular Docking Study: Identification of Potential Inhibitors in Lavandula Angustifolia Essential Oil Against the Main Protease of Sars-Cov-2 - Sahiroh, Samakhatus; Sulisti, Wahyu; Sunnardianto, Gagus Ketut; Setiadipura, Topan; Kharomah, Iklimatul (Computational And Experimental Research In Materials And Renewable Energy, 2023)
SARS-CoV-2, also known as, Covid-19 is an almost globally endemic disease that has infected hundreds of millions of people and caused ongoing deaths. Researchers are still trying to search for effective drugs against Covid-19. Currently, with the development of science and technology, the process of drug discovery through simulated environments is becoming increasingly accurate and yielding rapid results. The protease crystal structure of Covid-19 plays a crucial role in viral replication and represents promising primary targets for antiviral drug discovery and therapy. Lavender and N3 compound ligands were used as test ligands. A total of 9 lavender ligand compounds were subjected to testing using the molecular docking method. Molecular docking aims to achieve the optimal conformation of both the protein and ligand, as well as the relative orientation between them. The analysis conducted during molecular docking includes the determination of the inhibition constant and the study of interactions between the protein and ligand.Keywords: Covid-19, docking, N3, ligand